POSTSTENOTIC DILATION OF THE ASCENDING AORTA AS A RISK FACTOR IN AORTIC VALVE REPLACEMENT (Conferencea, 2023)
Evaluation of the effect of poststenotic dilation of the ascending aorta on the results of surgical treatment of patients with aortic valve defect.